Factors affecting employees’ turnover intention in construction companies in Klang, Selangor - Suhaidah, Hussain; Xian, See Huei (KnE Social Sciences, 2019)
This research is about factors affecting employees’ turnover intention in construction companies. Employees’ turnover intention is known as the organization’s workers’ intent or plan to leave their current working place’s position. Malaysia has scored third highest voluntary turnover rate, which is 9.5% in Southeast Asia year 2015. Most of the construction projects are difficult and complex to manage it. High employees’ turnover rate may influence the construction companies’ productivity and performances. There are many factors that will affect employees’ turnover intention, such as colleague relations, organizational commitment, organizational justice, organizational reputation, communication, and organizational politics. In order to address the issues above, this research was aims to identify the factors affecting employees’ turnover intention and to determine the relationship between the factors and employees’ turnover intention. Therefore, in order to achieve these objectives, a questionnaire survey involving 160 employees conducted to Grade 7 construction company in Klang, Selangor. There was 73 companies’ worker who responded to the survey. The data analysis conducted using SPSS and SmartPLS, and the results showed that organizational politics were mostly caused employees’ turnover intention in construction companies. The findings also showed that communication and organizational politics had a negative relationship with employees’ turnover intention. Results from this research can provide the evidence and bring convince for the construction companies in Malaysia to reduce employees turnover rate. In the future, the scope of the study can be expanded to other states of Malaysia to improve the reliability of this study.